2019
DOI: 10.1038/s41598-019-51446-9
|View full text |Cite
|
Sign up to set email alerts
|

Cereblon gene variants and clinical outcome in multiple myeloma patients treated with lenalidomide

Abstract: Carfilzomib-lenalidomide-dexamethasone (KRd) therapy has yielded promising results in patients with newly diagnosed multiple myeloma (NDMM). Cereblon (CRBN) is the direct molecular target of lenalidomide and genetic polymorphisms in CRBN have been associated with lenalidomide efficacy. In this study, we assessed the correlation of five single nucleotide variants (SNVs) in the CRBN gene with clinical response and outcomes in patients with NDMM administered KRd therapy with lenalidomide maintenance, achieving fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Moreover, we and others (24) have also identified novel binding protein of IMiDs, such as TP53regulating kinase, which may broaden their clinical utility. However, most MM cells eventually acquire resistance to IMiDs, which has, to date, been attributed to decreased expression of CRBN and rarely CRBN mutations (50,51). Defining mechanisms underlying clinical resist ance to IMiDs is therefore essential to inform the design of novel strategies to restore and/or enhance IMiD sensistivity and improve patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we and others (24) have also identified novel binding protein of IMiDs, such as TP53regulating kinase, which may broaden their clinical utility. However, most MM cells eventually acquire resistance to IMiDs, which has, to date, been attributed to decreased expression of CRBN and rarely CRBN mutations (50,51). Defining mechanisms underlying clinical resist ance to IMiDs is therefore essential to inform the design of novel strategies to restore and/or enhance IMiD sensistivity and improve patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies recognized an association between CRBN expression levels and response to IMIDs in MM. Therefore, SNVs in the CRBN gene have been investigated, but their role remains controversial due to the small number of patients [50,51].…”
Section: Mechanisms Of Dna Damage In MMmentioning
confidence: 99%
“…This molecule is part of an E3-ubiquitin ligase complex (CRL4 CRBN ), acting as a substrate receptor that recognizes speci c targets for ubiquitination, leading to further degradation by the ubiquitin-proteasome system 14 . More recently, it was shown that CRBN is necessary for the e cacy of thalidomide and its analogs lenalidomide and pomalidomide (named immunomodulatory drugs -IMiDs) in the treatment of MM [15][16][17][18][19] . Several studies have investigated the Thalidomide-CRBN interaction with regard to the teratogenic, immunomodulatory and therapeutic effects of the drug.…”
Section: Introductionmentioning
confidence: 99%